The correlation between the STOP-Bang score and oxygen saturation during spinal anesthesia with dexmedetomidine sedation - Minsu Yun; Jiwook Kim; Sungwon Ryu; Seo Han; Yusom Shin (Anesthesia and Pain Medicine, 2021)
Background The STOP-Bang questionnaire is a simple screening tool with high sensitivity for the detection of severe obstructive sleep apnea. Predicting airway obstruction would allow the safe management of sedative patients to prevent intraoperative hypoxia. This study was designed to check the correlation between the STOP-Bang score and oxygen saturation (SpO2) during sedation and confirm the availability of the STOP-Bang questionnaire as a preoperative exam for predicting the incidence of hypoxia in sedative patient management. Methods This study included 56 patients who received spinal anesthesia. The pre-anesthesia evaluation was conducted using the STOP-Bang questionnaire. The patients were under spinal anesthesia with an average block level of T10. Dexmedetomidine was infused with a loading dose of 1 μg/kg over 10 min and a maintenance dose of 0.5 μg/kg/h until the end of the procedure. The SpO2 of the patients was recorded every 5 min. Results The STOP-Bang score was negatively correlated with the lowest SpO2 (coefficient = –0.774, 95% confidence interval [CI]: –0.855 to –0.649, standard error [SE] = 0.054, P < 0.001). The item of “observed apnea” was the most correlated one with hypoxic events (odds ratio = 6.00, 95% CI: 1.086 to 33.145). Conclusions The STOP-Bang score was significantly correlated with the lowest SpO2 during spinal anesthesia, which enabled the prediction of meaningful hypoxia before it occurred in the sedated patients.